From Made-in-China to Made-in-Nigeria- A case for Nigeria as the new face of BRICS - Charles Okeke (Journal of Research and Multidisciplinary, 2023)
The term BRICS, originally introduced by Goldman Sachs economist O'Neill in 2001, stands for Brazil, Russia, India, China, and South Africa. By 2030, the group is expected to account for one-third of the world's output, with combined foreign reserves worth $4 trillion and making up around 17% of global trade. Nigeria and South Africa have gained attention due to their political and economic advancements in the twenty-first century, and Nigeria has been predicted to be suitable for the formation of groups like MINT, which includes Mexico, Indonesia, Nigeria, and Turkey. This study argues that Nigeria and BRICS could achieve their goals if they work together, as Nigeria's development would benefit from the size of BRICS economies, their economic potential, and the rising global demand for goods. Furthermore, Nigeria's recent economic growth, rapid industrialization, and consistently low labor costs with a workforce of over 200 million highlight the country's potential as a significant missing component in the BRICS equation. With a median age of 18 and a young population aged 15 to 65, Nigeria has one of the youngest populations in the world. China's incredible ascent has been a major theme in the BRICS story, as its sustained growth has changed the distribution of economic power worldwide.